The transcription factor EGR1 regulates metastatic potential of v-src transformed sarcoma cells - Cermák, Vladimír; Kosla, Jan; Plachý, Jirí; Trejbalová, Katerina; Hejnar, Jirí; Dvorák, Michal (Cellular and molecular life sciences, 2010)
Metastatic spreading of cancer cells is a highly complex process directed primarily by the interplay between tumor microenvironment, cell surface receptors, and actin cytoskeleton dynamics. To advance our understanding of metastatic cancer dissemination, we have developed a model system that is based on two v-src transformed chicken sarcoma cell lines-the highly metastatic parental PR9692 and a non-metastasizing but fully tumorigenic clonal derivative PR9692-E9. Oligonucleotide microarray analysis of both cell lines revealed that the gene encoding the transcription factor EGR1 was downregulated in the non-metastatic PR9692-E9 cells. Further investigation demonstrated that the introduction of exogenous EGR1 into PR9692-E9 cells restored their metastatic potential to a level indistinguishable from parental PR9692 cells. Microarray analysis of EGR1 reconstituted cells revealed the activation of genes that are crucial for actin cytoskeleton contractility (MYL9), filopodia formation (MYO10), the production of specific extracellular matrix components (HAS2, COL6A1-3) and other essential pro-metastatic abilities.
Keywords: kur domácí; Gene Expression Regulation, Neoplastic; nádorová transformace buněk; onkogenní protein pp60(v-src); Neoplasm Metastasis; Cell Line; fenotyp; Early Growth Response Protein 1; Phenotype; protein 1 časné růstové odpovědi; Cell Proliferation; Chickens; regulace genové exprese u nádorů; Cell Transformation, Neoplastic; Cytoskeleton; stanovení celkové genové exprese; sarkom; buněčná adheze; Cell Movement; Gene Expression Profiling; Oncogene Protein pp60(v-src); kinetika; Animals; zvířata; pohyb buněk; cytoskelet; Sarcoma; buněčné linie; proliferace buněk; metastázy nádorů; Kinetics; Cell Adhesion